P07.27 Performance of herpeselect elisa for diagnosis of hsv-1 and hsv-2 infection in a clinical setting. (13th September 2015) - Le, Q; Warren, T; Selke, S; Magaret, A; Wald, A
Abstract : Introduction: Focus HerpeSelect type specific ELISA is the most commonly used commercial assay for detection of HSV-1 and HSV-2 serostatus. We evaluated the accuracy of the HerpeSelect ELISA in patients who were seeking to confirm their serostatus with the University of Washington Western blot (UW WB). Methods: We reviewed charts of all persons who were tested for HSV antibody at the Westover Heights Clinic in Portland, OR between July 2010 and April 2014, and who were tested with both HerpeSelect ELISA and UW WB. Results: We evaluated test results on 442 persons, of whom 49% were women, with a median age of 36 (range 18–68). Overall, by UW WB, 61 persons tested HSV-2 seropositive only, 81 tested HSV-1 and HSV-2 seropositive, 170 were HSV-1 seropositive only, and 130 were seronegative for an overall HSV-2 prevalence of 32% and HSV-1 prevalence of 57%. Among 199 persons who tested HSV-2 positive on HerpeSelect ELISA according to manufacturer's cutoff of index value ³1.1, 58% confirmed by the UW WB. Among 131 persons with an index value 1.1–2.9, 50% confirmed; among 37 persons with an index value ≥3, 81% confirmed with the UW WB (c 2 test, p = 0.0007). The risk of false positive HSV-2 results was similar among persons with and without HSV-1 antibody (44% vs 39%, c 2 test, p = 0.41). Among 156 persons who tested HSV-2 negative by ELISA, 2% were found UW WB positive. Among 143 persons who tested HSV-1 positive by ELISA, 133 (92%) confirmed by the UW WB. However, an additional 49 persons were HSV-1 seropositive by UW WB but negative by the ELISA, for a negative predictive value of 72%. Conclusion: HerpeSelect ELISA has poor positive predictive value for HSV-2 and poor negative predictive value for HSV-1 in clinical practice. More accurate commercially available tests are needed for HSV antibody diagnostics. Disclosure of interest statement: No pharmaceutical grants were received for this study.